ANALISIS GERAKAN SHOLAT DHUHA TERHADAP PENGUATAN POSTUR TUBUH ANAK USIA 4-5 TAHUN DI RA AL IZZAH SERANG BANTEN - Ratna Setiawati; Fadlullah; Luluk Asmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the contribution of each movement in Dhuha prayer to strengthening the body posture of children aged 4-5 years at RA Al-Izzah Serang, Banten. The research employed a qualitative descriptive method with eight children from Group A as research subjects. Data were collected through observations in seven Dhuha prayer sessions, interviews with the principal and classroom teacher, and documentation. Data analysis used an interactive model comprising data reduction, display, and conclusion drawing. The findings reveal that each movement in Dhuha prayer contributes specifically to postural strengthening: standing (qiyam) develops balance and spinal alignment; bowing (ruku') enhances back flexibility; standing after bowing (i'tidal) trains dynamic balance; prostration (sujud) strengthens arms and shoulders; sitting (jalsa and tasyahud) improves hip and ankle joint flexibility. Children who regularly performed Dhuha prayer demonstrated more controlled movements, better postural stability, and improved body coordination. Therefore, Dhuha prayer serves not only as an act of worship but also as an activity supporting children's holistic physical development. Keywords: Dhuha prayer, body posture, early childhood, physical development, habituation.